Functional measurement of mitogen-activated protein kinase pathway activation predicts responsiveness of RAS-mutant cancers to MEK inhibitors. (May 2021) - Kato, Shumei; Porter, Robert; Okamura, Ryosuke; Lee, Suzanna; Zelichov, Ori; Tarcic, Gabi; Vidne, Michael; Kurzrock, Razelle
Abstract: Background: RAS variant–related functional impact on the mitogen-activated protein kinase (MAPK) pathway, and correlation between MAPK activation and MAPK/ERK kinase (MEK) inhibitor responsiveness, is not established. Patients and methods: Of 1, 693 tumours sequenced, 576 harboured a RAS alteration; 62 patients received an MEK inhibitor (MEKi) and had RAS mutations that were functionally characterised. We report that RAS mutants have variable levels of MAPK activity, as measured by a functional cell-based assay that quantified MAPK pathway activation after transfection with a variety of RAS mutations. Results: Patients with tumours harbouring RAS alterations with high versus low MAPK activity who were treated with an MEKi showed significantly longer median progression-free survival (PFS) (5.0 vs. 2.3 months; p = 0.0034) and overall survival (20.0 vs. 5.0 months; p = 0.0146) and a trend towards higher rates of clinical benefit (stable disease ≥6 months or partial/complete remission) (38% versus 15%; p = 0.095) (p-values as per univariate analysis). PFS remained statistically significant after the multivariate analysis (p = 0.003). Conclusions: These results support a correlation between RAS -mutant cancers with greater MAPK signalling and PFS after MEKi treatment. Highlights: Various RAS mutations and impact of the mitogen-activated protein kinase (MAPK)/ERK kinase (MEK) inhibitor is not well established. RAS mutants have variable levels of MAPK activity as assessed by a functional assay. High MAPK activity demonstrated longer progression-free survival with MEK inhibitors.